Chronostratigraphic Studies of the Ootun Area Revealing the Late Holocene Plume Volcanism of the Oldoinyo Lengai, Ngorongoro, Tanzania. (5th September 2022) - Makongoro, Mohamed Zengo; Vegi, Maheswara Rao; Vuai, Said Ali Hamad; Msabi, Michael Mwita
Abstract : Oldoinyo Lengai has been a subject of international attention for geoscientists because of its uniqueness. The mountain is the world's only active natrocarbonatite volcano whose recent activities are well documented. However, little is known about its eruptive history during the Holocene. One way of uncovering past volcanic activities is through chronostratigraphic studies. A rare stratigraphic sequence in the Ootun area containing buried tephra beds and paleosols is presented in this article. The beds suggest that the nearby active Oldoinyo Lengai volcano experienced the main plume volcanism during the late Holocene. This work presents the lithology of the area, estimated deposition period, and elemental and mineralogical compositions of strata, and establishing similarities between ash properties and information from previously reported chemistry and eruptions of the Oldoinyo Lengai volcano. Energy dispersive X-ray fluorescence, X-ray diffractometry, and accelerated mass spectrometry techniques were used for elemental, mineralogical, and radiocarbon dating analyses. A 1.3-m vertical soil profile revealed three major strata: topsoil, tephra bed, and paleosols. The paleosols are presumed to have been topsoil of the Ootun area during the Holocene. Subsurface tephra layers were found to contain similar properties to the volcanic material of the Oldoinyo Lengai. Based on the experimental findings and literature data, the study reports the occurrence of two major plume eruption events from the Oldoinyo Lengai, which happened around the minimum (oldest) age of 490 ± 10   BC and 771 AD. This work is essentially important in demonstrating the relevance of the region's tephra chronostratigraphic studies by revealing the prospect of collecting additional scientific data on past geological processes and paleoenvironmental conditions of northern Tanzania.